Supporting the design of network-spanning applications - Rennick Egglestone, Stefan; Boucher, Andy; Rodden, Tom; Law, Andy; Humble, Jan; Greenhalgh, Chris; Greenberg, Saul (ACM Press, 2009)
In this case study, we describe our use of ECT, a tool intended to simplify the design and development of network-spanning applications. We have used ECT throughout the course of a two-year collaboration, which has involved individuals with expertise in a variety of fields, including interaction design and computer systems engineering. We describe our experiences with this tool, with a particular focus on its emerging role in helping us to structure our collaboration. We conclude by presenting lessons that we have learned, and by suggesting future directions for the development of tools to support the design of network-spanning applications.